Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021 International Joint Conference on Neural Networks (IJCNN) 2021
DOI: 10.1109/ijcnn52387.2021.9534091
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of AutoML Tools for Machine Learning, Deep Learning and XGBoost

Abstract: This paper presents a benchmark of supervised Automated Machine Learning (AutoML) tools. Firstly, we analyze the characteristics of eight recent open-source AutoML tools (Auto-Keras, Auto-PyTorch, Auto-Sklearn, AutoGluon, H2O AutoML, rminer, TPOT and TransmogrifAI) and describe twelve popular OpenML datasets that were used in the benchmark (divided into regression, binary and multi-class classification tasks). Then, we perform a comparison study with hundreds of computational experiments based on three scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 21 publications
0
28
0
3
Order By: Relevance
“…Various open-source platforms, such as AutoKeras, AutoPyTorch, AutoSklearn, AutoGluon, and H2O AutoML, have been developed to facilitate the adoption of AutoML [ 46 ]. Previous studies [ 47 , 48 ] have demonstrated the strong feature of H2O AutoML for processing large and complicated datasets by quickly searching the optimal model without the need for manual trial and error.…”
Section: Methodsmentioning
confidence: 99%
“…Various open-source platforms, such as AutoKeras, AutoPyTorch, AutoSklearn, AutoGluon, and H2O AutoML, have been developed to facilitate the adoption of AutoML [ 46 ]. Previous studies [ 47 , 48 ] have demonstrated the strong feature of H2O AutoML for processing large and complicated datasets by quickly searching the optimal model without the need for manual trial and error.…”
Section: Methodsmentioning
confidence: 99%
“…They evaluated all data using TPOT and showed that the larger the dataset the better the optimization of the classifiers works using TPOT. Ferreira et al carried out experiments based on three scenarios: General ML (GML), Deep Learning (DL) and XGBoost [27]. They performed a 10-fold cross-validation comparing eight open-source AutoML tools on 12 popular OpenML datasets.…”
Section: Optimization Using Tpot-automlmentioning
confidence: 99%
“…Diversos trabalhos recentes avaliam ou propõe ferramentas de AutoML para diferentes contexto e domínios [Nagarajah and Poravi, 2019, Ferreira et al, 2021, Bezrukavnikov and Linder, 2021, Truong et al, 2019, Karmaker et al, 2021. Há estudos recentes (e.g., [Nagarajah andPoravi, 2019, Karmaker et al, 2021]) que apresentam análises de dezenas de trabalhos de AutoML, observando as particularidades de diferentes ferramentas, como Auto-Weka, Hyperopt-Sklearn, TPOT, AutoCompet e PennAI, e apontando desafios na área, como interpretabilidade, transparência, níveis de personalizac ¸ão e recursos de depurac ¸ão.…”
Section: Trabalhos Relacionadosunclassified
“…Em [Ferreira et al, 2021], os autores apresentam um estudo comparativo entre aplicac ¸ões de AutoML quanto a machine learning, deep learning e XGBoost. As ferramentas Auto-Keras, Auto-PyTorch, Auto-Sklearn, AutoGluon, H2O AutoML, rminer, TPOT e TransmogrifAI foram avaliadas com relac ¸ão ao tempo de execuc ¸ão e desempenho de predic ¸ão em doze datasets, disponíveis na plataforma OpenML 7 , em diferentes domínios de aplicac ¸ão, como a área médica (diagnóstico de doenc ¸as cardíacas, concentrac ¸ão de plasma e diabetes), métodos contraceptivos e classificac ¸ão de risco de um cliente para concessão de crédito.…”
Section: Trabalhos Relacionadosunclassified
See 1 more Smart Citation